ANALISIS KEMAMPUAN PASSING DALAM PERMAINAN SEPAKBOLA PADA SSB BANGAU PUTRA - Achmad Karim (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This study aims to determine the level of passing ability in the Bangau Putra Football School (SSB Bangau Putra). This research is a descriptive quantitative study. The method used is a survey, and data collection techniques include tests and measurements. The population in this study was the entire Bangau Putra Football School (SSB Bangau Putra). Since all participants were sampled, this study is a population study of 30 Bangau Putra Football Schools. The instrument used was a football passing test. The data analysis technique used percentage descriptions. The results show that the level of passing ability in the Bangau Putra Football School (SSB Bangau Putra) was in the